2018
DOI: 10.1177/0886260518798359
|View full text |Cite
|
Sign up to set email alerts
|

Oil Development and Intimate Partner Violence: Implementation of Section 8 Housing Policies in the Bakken Region of North Dakota and Montana

Abstract: One of the challenges survivors of intimate partner violence (IPV) often face is securing safe and affordable housing. Many survivors qualify for public housing programs such as the Section 8 Project-Based Rental Assistance (PBRA) program and tenant-based Housing Choice Voucher Program (HCVP). These programs can be vital for survivors fleeing abuse and trying to rebuild their lives. But how might regional conditions such as rapid population growth resulting from an oil boom affect the implementation of such pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 33 publications
0
13
0
Order By: Relevance
“…Some permanent residents, such as seniors or individuals on fixed incomes, leave the community after their living costs become unaffordable. Subsidized housing is seldom a viable option for newcomers or permanent residents as the rates paid by the government are a fraction of the inflated market prices (Jayasundara et al, 2018). Losing permanent residents, and especially seniors, due to unaffordable housing reduces the informal social control in these communities.…”
Section: Precarious Housing Arrangementsmentioning
confidence: 99%
See 1 more Smart Citation
“…Some permanent residents, such as seniors or individuals on fixed incomes, leave the community after their living costs become unaffordable. Subsidized housing is seldom a viable option for newcomers or permanent residents as the rates paid by the government are a fraction of the inflated market prices (Jayasundara et al, 2018). Losing permanent residents, and especially seniors, due to unaffordable housing reduces the informal social control in these communities.…”
Section: Precarious Housing Arrangementsmentioning
confidence: 99%
“…Section 8, or subsidized housing, is an option for victims of family violence, but after a boom occurs these benefits are almost impossible to access. In their analysis of housing in the Bakken, Jayasundara et al (2018) found that eligibility restrictions prevented some survivors from accessing this housing as landlords opted out of the Section 8 program after rents increased. As a result, even when survivors of family violence are approved for subsidized housing, they are unable to find lodging within the approved budget.…”
Section: Precarious Housing Arrangementsmentioning
confidence: 99%
“…They noted that women often follow their partners to boomtowns and owing to the lack of gainful employment opportunities, they become dependent on their partners. Similarly, Jayasundara et al (2018) found that in the Bakken region of North Dakota and Montana in the US, the oil and natural gas boom increased women's vulnerability owing to a lack of available and affordable housing from which to escape violent situations. Participants in our study also explained the increase in domestic violence as being closely related to the instability of the industry as it puts stress on workers.…”
Section: Discussionmentioning
confidence: 99%
“…Also, women's lack of employment opportunities in lucrative extractive industry jobs makes it difficult to find affordable housing. For example, in addition to the inflated housing and rent prices that put many housing accommodations in boomtowns out of economic reach, there are long wait periods for subsidized housing in boomtowns, which puts single mothers and women working to escape intimate partner violence at a particular disadvantage (Jayasundara et al, 2018). Affordable childcare is also hard to find in boomtown areas which limits women's employment options and furthers women's economic dependence on their partners (Fernando & Cooley, 2016;Ruddell, 2017).…”
Section: The Gendered Impacts Of Boomtown Livingmentioning
confidence: 99%
“…With the exception of Fort McMurray, Alberta, however, very few of these places receive much attention as they are often small towns in rural and remote places that are both out of sight and out of mind. The challenges created by rapid population growth, however, are of critical importance to the residents, as well as the workers in the health, education, social service, and justice systems who must respond to escalating demands for services with inadequate resources (Jayasundara, Danis, Legerski et al, 2018).…”
mentioning
confidence: 99%